1998
DOI: 10.1046/j.1365-2141.1998.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of computerized decision support systems for oral anticoagulation management

Abstract: Summary. Computerized decision support systems (CDSS)are available to assist clinicians in the therapeutic management of oral anticoagulation. We report the findings relating to CDSS for oral anticoagulation management of a primary-care-based systematic review which largely focused on near-patient testing. Seven papers were reviewed which covered four different systems. The methodology of these papers was generally poor, although one randomized controlled trial showed improved therapeutic control associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 15 publications
1
32
0
1
Order By: Relevance
“…Finally, various other strategies have been suggested to improve the safety of anticoagulation therapy including computer decision support systems, 123 the use of patient self-monitoring devices 124 and the use of drugs that inhibit other targets in the anticoagulation pathway, for example the oral thrombin inhibitors. 125 Whether we should use pharmacogenetic-based warfarin therapy in competition or in conjunction with these other approaches is not clear.…”
Section: Wadelius and M Pirmohamedmentioning
confidence: 99%
“…Finally, various other strategies have been suggested to improve the safety of anticoagulation therapy including computer decision support systems, 123 the use of patient self-monitoring devices 124 and the use of drugs that inhibit other targets in the anticoagulation pathway, for example the oral thrombin inhibitors. 125 Whether we should use pharmacogenetic-based warfarin therapy in competition or in conjunction with these other approaches is not clear.…”
Section: Wadelius and M Pirmohamedmentioning
confidence: 99%
“…Besides, they may enable non-specialist clinicians or nurses to undertake AO control in primary care centres. Several programs have been developed to generate AO doses with good results [4,[7][8][9][10]. In a multicentre Marco/Sedano/Berm煤 dez/L贸 pez-Duarte/ Fern谩 ndez-Fontecha/Zubizarreta randomised study of 285 patients, a significant benefit was found in achieving target INR in the group of stable patients when doses were calculated by the computer [11].…”
Section: Introductionmentioning
confidence: 99%
“…Others assessed the effects of CDSSs for a specific clinical outcome, such as oral anticoagulation management but only stated that a review had not been completed in that area without justifying why it might have different results [14]. Authors such as Kawamoto et al [23] conducted specific analyses that had not been done before, such as conducting a meta-analysis; however, given that they did not justify the conduct of a review in their specific topic area, they were still classified as having ''no justification.''…”
Section: Justification Of Decisions About Scope Of Reviewsmentioning
confidence: 98%
“…Condition [9,14,16,20,22,25,28,33,34] 9 Setting [13,19,24] 3 Study design [5,23] 2 Population [27,32] 2 Outcome [31] 1 Total 17 54.8…”
Section: Number Of Splits Characteristic Of Split No % Onementioning
confidence: 99%